ASSESSMENT OF GROUNDWATER QUALITY IN ULUOVA, ELAZIG, TURKEY - Tunc, Muslun Sara; Tepe, Ozlem; Unlu, Ayhan; Dursun, Arzu Y.; Yaman, Mehmet (Parlar Scientific Publications (P S P), 2017)
The Uluova (Elazig) plain is located in the west of East Anatolia Region and in the 15 km northeast of Eastern Anatolia Fault Zone. The water supplied from the wells in Uluova region is used as drinking, domestic and irrigation water. In the study, the groundwater samples were taken from several wells in Uluova region in March, April, May and September 2007 and March and April 2014 to examine the quality of groundwater in the Uluova region, Elazig, Turkey. They were assayed for quality parameters including pH, electrical conductivity (EC), total dissolved solids (TDS), hardness, NH4-N, NO2-N, NO3-N, sulfate, chloride, Ca2+, Mg2+, Na+, K+, Al, Cd, Pb, Ni and total and fecal coliforms. The results obtained were checked against the national and international drinking water standards and indicated that the groundwater samples were utilizable as drinking water based on the physical and the chemical parameters analyzed. Moreover, its suitability for irrigation purpose was evaluated in terms of sodium percentage (Na %) and sodium adsorption ratio (SAR). It was determined that the obtained concentrations of cadmium, lead, nickel and aluminum were lower than the guideline values; the studied water samples were appropriate for both drinking and irrigation purpose.
Keywords: Groundwater; Turkey; Uluova; Water quality